Microencapsulation of Tangeretin in a Citrus Pectin Mixture Matrix - Xiuxiu Sun; Randall G. Cameron; John A. Manthey; Wayne B. Hunter; Jinhe Bai (Foods, 2020)
The objectives of this research were to microencapsulate tangeretin, and to evaluate the basic characteristics of the microcapsule products. Tangeretin is a polymethoxyflavone (PMF) which has been revealed to possess various health benefits and is abundant in tangerine and other citrus peels. Microencapsulation technology is widely employed in the food and pharmaceutical industries to exploit functional ingredients, cells, and enzymes. Spray drying is a frequently applied microencapsulation method because of its low cost and technical requirements. In this research, tangeretin dissolved at different concentrations in bergamot oil was microencapsulated in a citrus pectin/sodium alginate matrix. The resulting microcapsule powder showed promising physical and structural properties. The retention efficiency of tangeretin was greater at a concentration of 2.0% (98.92%) than at 0.2% (71.05%), probably due to the higher temperature of the emulsion during the homogenizing and spray-drying processes. Encapsulation efficiency was reduced with increased concentration of tangeretin. Our results indicate that tangeretin could be successfully encapsulated within a citrus pectin/sodium alginate matrix using bergamot oil as a carrier.